Precision Full-Wave Rectifier Using Two DDCCs - Montree Kumngern (My University, 2011)
A new precision full-wave rectifier employing only two differential difference current conveyors, which is very suitable for CMOS technology implementation, is presented. The proposed rectifier is the voltage-mode circuit, which offers high-input and low-output impedance hence it can be directly connected to load without using any buffer circuits. PSPICE is used to verify the circuit performance. Simulated rectifier results based-on a 0.5 µm CMOS technology with ±2.5 V supply voltage demonstrates high precision rectification and excellent temperature stability. In addition, the application of proposed rectifier to pseudo RMS-to-DC conversion is also introduced.
Keywords: Rectifier (neural networks); Precision rectifier; Peak inverse voltage; Analog and Mixed-Signal Circuit Design